Wakaf Tanah Ulayat sebagai Solusi Peralihan Hak Atas Tanah Ulayat Secara Permanen di Sumatera Barat - Mirwati, Yulia; Faisal, Yontri; Zahara, Zahara; APHA, Journal Manager (Asosiasi Pengajar Hukum Adat (APHA) Indonesia, Fakultas Hukum Universitas Trisakti - Jakarta Barat, Indonesia, 2018)
Article 3 of the Basic Regulation of Agrarian Affairs/PeraturanDasarPokokpokokAgraria (UUPA) recognizes the existence of communal land (communal right). This recognition of communal rights has been planned since the beginning of the drafting of the national agrarian bill; therefore, the legal concept of agrarian reform is stipulated with customary law in it. In West Sumatra, the existence of communal rights is still strong. The transfer of communal rights cannot be done in a permanent manner, only temporary, such as a pawning which is now referred to as Salang Pinjam in Minang or Padang language, and even then with very strict requirements, because the principle, in Minang language, is that communal land is: jua indak dimakan balig adai indak dimakan sendo (it cannot be traded,and when it ispawned, it is with strict conditions). Utilization of communalland for outsiders is a temporary nature, limited by time and will not eliminate the communal rights. This is, in its customary law, called Kabau Pai Kubangan Tingga, and this is done with the agreement of the customary law community through leaders of customs. In addition, Minang or Minangkabau customs are integrated with the concept of Islamic law; this is confirmed in the fatwa or decision: adat basandi syarak dan syarak basandi kitabullah. At the same time, the Waqf Institute is also developing well in Minangkabau. One of the objects of the waqf is communalland, and its allotment is especially for places of worship, education, health and others, which are still not oriented to the development of productive economies. In the waqf arrangement in Indonesia, communalland is not formally seen as the object,however,since in the past, the Minangkabau customary law communities have been carrying out thewaqf of communalland, even though without registration. It is further found thatwaqf of communalland is a solution to transferring of the communalland permanently to the indigenous peoplethrough the management of nadzir (recipient of waqf), because the waqf of communalland lasts forever.